ONLINE ORDERING SYSTEM ON BAKERY WEBSITE - Annisa Rizki Agusti; M. Fauzan Fachruzi Rauf; Rosa Triana Putri; Tarisa Riani Rizki Tanjung; Teuku Naufal Atha (Sean Institute, 2023)
This article reviews the literature on online ordering systems for bakery websites. This article discusses the development of an online ordering system for bakery websites using qualitative research methodology. This paper proposes an e-commerce bakery system that allows bakery owners and customers to manage their daily activities in ordering online. The bakery's website serves as an online storefront, which allows customers to browse the bakery's products, place orders, and pay for them conveniently. This research concludes that an online ordering system is an effective way to allow customers to order their food online without the need to go to the store to buy it.